Sequelae Tuberkulosis dengan Hemoptisis Rekurens: [Recurrent Hemoptysis in Sequelae Tuberculosis] - Desilia Atikawati; Isnin Anang Marhana (Faculty of Medicine Universitas Airlangga, 2015)
Background: Various sequelae and complications can occur in treated or untreated tuberculosis (TB). One of complications in the lungs is hemoptysis, due to alterations of pulmonary vascular structure. Hemoptysis as TB sequelae can happen recurrently and massively. Case: We present the case of 31 year old man with recurrent hemoptysis since 1 year before admitted to hospital. Patient had a history of receiving antituberculosis drugs (ATD) before. Chest xray showed pleural thickening and opacity in right hemithorax with signs of loss of volume. Bronchoscopy showed active bleeding in lateral segment of right lung middle lobe. Chest CT showed destroyed right lung. Hemoptysis still existed despite the given conventional therapy, thus patient underwent pulmonary arteriography. The result showed extensive vascular abnormality in the right lung with arteriovenous fistula on right bronchial artery and aneurysmatic branch of superior bronchial and inner intercostal arteries. During the procedure, there was no active bleeding, so bronchial artery embolization was adjourned. Patient then experienced recurrent and massive hemoptysis, thus right pneumonectomy was done. During the surgery, there was uncontrolled active bleeding that caused the patient’s death. Conclusion: This case illustrates recurrent hemoptysis as one of severe TB sequelae. In extensive pulmonary vascular abnormality, pneumonectomy can cause uncontrolled active bleeding. Bronchial artery embolization can be used as an alternative to treat patients with recurrent homptysis.